2013
DOI: 10.1177/0829573513491232
|View full text |Cite
|
Sign up to set email alerts
|

Youth Perceptions of Attention-Deficit/Hyperactivity Disorder and Barriers to Treatment

Abstract: The purpose of this study was to gain information about how youth with ADHD perceive this disorder and the barriers to treatment. Six focus groups were conducted in three locations within Nova Scotia (two of each: elementary school students, middle school students, high school students). Qualitative data was collected from 25 youth (aged 10 to 21) diagnosed with ADHD. Data analysis conducted through Ethnograph software revealed several themes: (a) participants did not perceive ADHD in a positive light; (b) you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 39 publications
(74 reference statements)
5
20
1
Order By: Relevance
“…Similar to the findings of other studies (Walker-Noack, Corkum, Elik, & Fearon, 2013;Andersson Frondelius, Ranjbar, Danielsson, 2019), also this study has showed that some children in some situations perceive their symptoms as empowering. It is important to explore those perceptions concerning possible contextual aspects related to them and aspects related to characteristics of those children.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the findings of other studies (Walker-Noack, Corkum, Elik, & Fearon, 2013;Andersson Frondelius, Ranjbar, Danielsson, 2019), also this study has showed that some children in some situations perceive their symptoms as empowering. It is important to explore those perceptions concerning possible contextual aspects related to them and aspects related to characteristics of those children.…”
Section: Discussionsupporting
confidence: 91%
“…Walker-Noack et al 37 conducted six focus groups with young people aged 10–21 years diagnosed with ADHD. The focus of the discussion was on the perceptions of the young people toward ADHD and the barriers to treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The authors suggest that the complex views of ADHD and its treatment held by young people may be defined as barriers to treatment adherence. 37 …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, beliefs about the effectiveness of medication coupled with minimal experience of side effects have been linked to willingness to use ADHD medication (Bussing et al, 2012). Negative beliefs about medication, for example about depletion of energy, have been reported in young persons between 10 and 21 years of age (Walker-Noack, Corkum, Elik, & Fearon, 2013).…”
Section: Beliefs About Medicationmentioning
confidence: 99%